네트워크 기반에서의 스마트 농업 표준 기준모델 분석 - 김동일; 정희창; Kim, Dong Il; Chung, Hee Chang (한국정보통신학회논문지, 2015)
IT convergence with agriculture is expected to bring more efficiency and quality improvement in producing, distributing, consuming of agricultural products with the aid of information processing and autonomous control technologies of the IT area. Smart Farming based on network is a service which is capable of coping with environmental and technical problems with the actualized IT convergence case for agriculture. In this paper, it is required to consider the actualized IT convergence case for agriculture, namely Smart Farming as a solution to cope the presented problems. In addition, propose and suggest to standard model and standardization items requirement for the Smart Farming based on network. IT 와 농업분야의 융합은 생산, 유통, 소비 분야에서의 효율과 질적 향상을 기대하게 되었고 특히 IT 영역의 정보 분석 기술과 자동제어 기술은 농산물 생산에 많은 장점을 제공하게 되었다. 네트워크 기반에서의 농업 분야 ICT확대는 기술적, 환경적인 측면에서의 어려움들을 해결하게 되었다. 본 논문에서는 IT와 접목한 스마트 농업 환경에서의 표준 기능 모델을 제안 분석하고 이를 바탕으로 한 스마트 농업에서의 기술적 서비스 요구조건 을 제시한다.